Rozwój kapitału ludzkiego poprzez efektywne zarządzanie pracownikami wiedzy - Morawski, Mieczysław (Developing Human Capital through Effective Management of Knowledge Workers, 2008)
The article presents stratified model of knowledge workers management. This model divides knowledge workers in four categories. Each category is being managed according to individual chosen personal programme. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 225-234